Katherine Mansfield and Russia - Kimber, Gerri; Martin, W. Todd; Diment, Galya (Katherine Mansfield studies, 2017)
This volume presents essays that engage with many aspects of Mansfield's response to all things Russian as well as to the Russians she met in England and France. In addition, the volume presents a collection of images of Gurdjieff's Institute at Fontainebleau, several of which have never been seen before.